Protection of agammaglobulinemic piglets from porcine rotavirus infection by antibody against simian rotavirus SA-11. - Lecce, J G (1991)
Rotavirus, a double-stranded RNA virus, has been implicated as a diarrhea-provoking agent in a variety of animal species. Several previous reports have shown that immunization with a single serotype may result in increased in vitro neutralization titers against serotypes not represented in the immunogen. This study was undertaken to determine whether antibody from cows immunized against simian rotavirus strain SA-11 (which is alien to pigs) could protect neonatal piglets from infection with a North Carolina isolate of porcine rotavirus. Accordingly, cows were immunized with SA-11 and an immunoglobulin G (IgG)-rich fraction was isolated from their colostrum. An IgG-rich fraction was similarly isolated from colostrum of nonimmunized cows. At equal concentrations, IgG from SA-11-immunized cows had two- to fourfold higher neutralization titers to seven of eight test strains of rotavirus, including SA-11 (serotype 3); human rotavirus serotypes 1, 3, and 4; North Carolina porcine rotavirus (serotype undetermined); Ohio State porcine rotavirus (serotype 5); and bovine rotavirus (serotype 6). The IgG-rich fractions were fed as dietary supplements to agammaglobulinemic piglets infected with the North Carolina porcine rotavirus. IgG from the SA-11-immunized cows was about eightfold more effective in protecting piglets than was IgG from nonimmunized cows.